2006
DOI: 10.1111/j.1572-0241.2006.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Autoimmune Hepatitis: Outcome and Risk Factors

Abstract: The presence of autoantibodies may be a risk factor for adverse pregnancy outcome in AIH patients. Close monitoring of both mother and fetus seems advisable due to a significant rate of maternal and fetal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
1
28

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(196 citation statements)
references
References 25 publications
7
150
1
28
Order By: Relevance
“…Although AIH was historically thought to be quiescent during pregnancy, more recent data suggest that AIH may have an initial presentation during pregnancy, an intrapartum fl are risk of >20% and postpartum fl are risk of up to 30-50% ( 124,125 ). Treatment for AIH is based on immunosuppression with corticosteroids and/or AZA, with recent practice guidelines for AIH recommending prednisone monotherapy for pregnant individuals ( 126 ).…”
Section: Autoimmune Hepatitismentioning
confidence: 99%
“…Although AIH was historically thought to be quiescent during pregnancy, more recent data suggest that AIH may have an initial presentation during pregnancy, an intrapartum fl are risk of >20% and postpartum fl are risk of up to 30-50% ( 124,125 ). Treatment for AIH is based on immunosuppression with corticosteroids and/or AZA, with recent practice guidelines for AIH recommending prednisone monotherapy for pregnant individuals ( 126 ).…”
Section: Autoimmune Hepatitismentioning
confidence: 99%
“…AIH affects young women, and it is common to be faced with a patient with established AIH who either wants to become pregnant or has already done so. Most patients with AIH can expect a good outcome, whereas higher rates of maternal and fetal problems are reported particularly in patients with type 2 or 3 AIH [9]. Unexplained adverse pregnancy outcomes were associated with antibodies to SLA/LP and Ro/SSA in the affected mothers [9].…”
Section: Aih and Pregnancymentioning
confidence: 99%
“…Most patients with AIH can expect a good outcome, whereas higher rates of maternal and fetal problems are reported particularly in patients with type 2 or 3 AIH [9]. Unexplained adverse pregnancy outcomes were associated with antibodies to SLA/LP and Ro/SSA in the affected mothers [9]. In addition, the disease may flare after delivery, as the pregnancy-associated immunosuppressive state is lost [167,168].…”
Section: Aih and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Long periods of subclinical disease may also ensue after presentation. Recent surveys of pregnancy in AIH have indicated that the initial presentations of AIH may occur not only during pregnancy but in the early post-partum period [14,15] . AIH may occur in conjunction with a variety of autoimmune disorders, including celiac disease [16,17] .…”
Section: Clinical Featuresmentioning
confidence: 99%